2017
DOI: 10.1007/s12520-017-0488-3
|View full text |Cite
|
Sign up to set email alerts
|

Who ate the birds: the taphonomy of Sarakenos Cave, Greece

Abstract: The taphonomic analysis of avian remains from Sarakenos Cave reveals that, contrary to previous suggestions, many bird bones excavated there represent food remains of the Eagle Owls rather than humans. The conclusion is based on the presence of traces of digestion, beak and claw punctures, and indirect evidence that includes relative preservation of particular elements, species composition, the lack of cut marks, and the absence of numerous traces of burning. Specimens with medullary bone and traces of digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Taphonomic analysis of individual shells considers abrasion, chemical dissolution, biodegradation, and thermal alteration (Claassen, 1998; Gutiérrez Zugasti, 2008–2009; Hammond, 2014). Taphonomic alterations for bone remains consider anthropic damage and nonanthropic damage (Bochenski et al, 2018; Fernandez‐Jalvo & Andrews, 2016; Johnson et al, 2016; Lyman, 1994a; Rick et al, 2006; Pokines & Symes, 2013). Density mediated attrition (Bar‐Oz & Munro, 2004) is measured by potential correlation of bone mineral density (BMD) (Borella et al, 2007; Elkin, 1995), through Spearman's ρ with observed %MAU (minimal animal unit) (Lyman et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Taphonomic analysis of individual shells considers abrasion, chemical dissolution, biodegradation, and thermal alteration (Claassen, 1998; Gutiérrez Zugasti, 2008–2009; Hammond, 2014). Taphonomic alterations for bone remains consider anthropic damage and nonanthropic damage (Bochenski et al, 2018; Fernandez‐Jalvo & Andrews, 2016; Johnson et al, 2016; Lyman, 1994a; Rick et al, 2006; Pokines & Symes, 2013). Density mediated attrition (Bar‐Oz & Munro, 2004) is measured by potential correlation of bone mineral density (BMD) (Borella et al, 2007; Elkin, 1995), through Spearman's ρ with observed %MAU (minimal animal unit) (Lyman et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Among the finds (e.g. pottery, lithics, figurines) were numerous ovis, capra, bos taurus, small mustelid, rodent and avian bones(91)(92)(93). The single bovine petrous bone used in this study has been recovered from trench F (layer 22, square 46) that is dated to c. 5750-5600 BC.…”
mentioning
confidence: 98%
“…Another group, the Macruromys, were common in this early level but are now very rare in the Highlands and absent from Mt Elimbari (see Table S3 for a comparison between present day fauna on Mt Elimbari and those present at Kiowa). Importantly, the small rats in this deposit also exhibit etching consistent with digestion and undoubtably derive from predator pellets, either a raptor (see Bochenski et al, 2018;Hawkins et al, 2018Hawkins et al, , 2019, or a quoll (see Miscamble and Manne, 2016). Birds of prey in the area are able to take down animals up to around 1 kg when they are on the ground, the size of small possums such as Pseudochirulus forbesi (Dwyer, 1983).…”
Section: Kiowa Faunal Remainsmentioning
confidence: 99%